In vitro assessment of mouse fetal abdominal aortic vascular function - Renshall, Lewis J. (American Physiological Society, 2014)
Fetal growth restriction (FGR) affects 3–8% of human pregnancies. Mouse models have provided important etiological data on FGR; they permit the assessment of treatment strategies on the physiological function of both mother and her developing offspring. Our study aimed to 1) develop a method to assess vascular function in fetal mice and 2) as a proof of principle ascertain whether a high dose of sildenafil citrate (SC; Viagra) administered to the pregnant dam affected fetal vascular reactivity. We developed a wire myography methodology for evaluation of fetal vascular function in vitro using the placenta-specific insulin-like growth factor II (Igf2) knockout mouse (P0; a model of FGR). Vascular function was determined in abdominal aortas isolated from P0 and wild-type (WT) fetuses at embryonic day (E) 18.5 of gestation. A subset of dams received SC 0.8 mg/ml via drinking water from E12.5; data were compared with water-only controls. Using wire myography, we found that fetal aortic rings exhibited significant agonist-induced contraction, and endothelium-dependent and endothelium-independent relaxation. Sex-specific alterations in reactivity were noted in both strains. Maternal treatment with SC significantly attenuated endothelium-dependent and endothelium-independent relaxation of fetal aortic rings. Mouse fetal abdominal aortas reproducibly respond to vasoactive agents. Study of these vessels in mouse genetic models of pregnancy complications may 1) help to delineate early signs of abnormal vascular reactivity and 2) inform whether treatments given to the mother during pregnancy may impact upon fetal vascular function.